ANALISA MANAJEMEN RESIKO DAN STRATEGI INVESTASI PADA FOREX ONLINE TRADING DAN PENGARUHNYA TERHADAP VALUE ADDED INVESTOR DI PT. MONEX INVESTINDO FUTURES - Hutabarat, Lawrence Hasiolan (Program Doktor Ilmu Ekonomi, 2010)
This research intend to study the influence of risk management and investment strategy over forex online trading and investor’s value added. Sample for this research is the investors who are doing forex online trading at PT. Monex Investindo Futures in Surabaya. This research is a predictive research and use quantitative method. Data analysis uses Structural Equation Modeling (SEM) and statistical tool Partial Least Square (PLS). The program that is used is Smart PLS Version 1.10 for Windows.This research use independent variables such as cutloss, switching, locking, averaging, momentum trading, technical trading, fundamental trading, short term, mid term, long term, trade based on risk management, trade based on investment strategy, trade based on risk management and investment strategy, increase, constant, and decrease. Dependent variables are risk management, investment strategy, , forex online trading and investor’s value added.This research proves that risk management and investment strategy influence significantly forex online trading and investor’s value added, and forex online trading influence significantly investor’s value added. This is shown by the result of data analysis using PLS that T-test value is more than 1,96 for all. Specifically for risk management, having negatif influence significantly over investor’s value added. This means that by doing risk management, in this case doing averaging, will lower the investor’s value added.Keywords : Risk management, investment strategy, forex online trading and and investor’s value added.